Rational Design Strategies for Development of Non-selective COX – Inhibitor Piroxicam: A Comprehensive Review - Meena, Rahul (International Journal of Pharmaceutical & Biological Archive, 2024)
The development of selective Cyclooxygenase (COX)-2 inhibitors, such as Piroxicam, represents a significant advancement in anti-inflammatory therapy, aiming to mitigate the gastrointestinal side effects associated with non-selective Non-steroidal anti-inflammatory drugs (NSAIDs). This comprehensive review delves into the rational design strategies employed in the development of COX-2 selective inhibitors, focusing on Piroxicam. The review begins with an overview of COX enzymes, their physiological roles, and the need for selective inhibition. It explores various design strategies, including structure-based drug design, which leverages crystallography and molecular modeling to identify key structural differences between COX-1 and COX-2. Ligand-based approaches, combinatorial chemistry, and computational methods, such as molecular docking and in silico screening, are discussed for their roles in optimizing lead compounds. The review also highlights chemical modifications and the development of Piroxicam analogs to enhance COX-2 selectivity. Mechanistic insights into the binding interactions and structure-activity relationships are provided, alongside a discussion on the pharmacokinetics and pharmacodynamics of Piroxicam. Clinical efficacy, safety profiles, and comparative analyses with other NSAIDs are examined to underscore the therapeutic potential and challenges of COX-2 inhibitors. The review concludes with future directions, emphasizing emerging strategies and the potential for personalized medicine in the continued evolution of COX-2 selective inhibitors.